Desigualdade de indicadores de mortalidade no Sudeste do Brasil - Cordeiro, Ricardo [UNESP]; Olivencia P, Eduardo R [UNESP]; Cardoso, Chrystiano F [UNESP]; Cortez, Daniela B [UNESP]; Kakinami, Eric [UNESP]; Souza, Jacques J G [UNESP]; Souza, Maria T M [UNESP]; Fernandes, Ricardo Augusto [UNESP]; Guercia, Rodrigo F [UNESP]; Adoni, Tarso [UNESP] (Universidade de São Paulo (USP), Faculdade de Saúde Pública, 1999)
INTRODUÇÃO: Há indícios de que a deterioração das condições de trabalho ocorrida em anos recentes influencie a mortalidade. O objetivo do estudo é estimar indicadores de mortalidade para a população de Botucatu, classificada de acordo com as ocupações exercidas. MÉTODO: Foram calculados os indicadores coeficiente de mortalidade padronizado (CMP), razão de risco padronizada e anos potenciais de vida perdidos (APVP) para a população de Botucatu, em 1997, segundo ocupações e causas básicas do óbito. RESULTADOS: Os indicadores CMP e APVP variaram entre 0,6 e 39,9 óbitos/1000 trabalhadores e entre 33 e 334 anos/1000 trabalhadores, respectivamente, de acordo com a ocupação principal exercida. Observou-se que a ordenação quantitativa das causas de óbito depende da ocupação e do indicador utilizado. CONCLUSÕES: Os indicadores de mortalidade verificados apresentam uma grande heterogeneidade quando analisados de acordo com ocupação e causas básicas de óbito, refletindo a enorme desigualdade social existente na população estudada.

INTRODUCTION: The main causes of illness and death in Brazil have been migrating backwards into the younger population during the last few years, increasing especially in the more productive age groups. Given the relationship between work and health/disease process, the hypothesis to be considered is that this phenomenon is partially due to the deterioration of workplace conditions. To contribute to investigating this hypothesis, this study estimates mortality risk indicators for the population of Botucatu, in the Southeast region of Brazil, classified according to their occupation. METHODS: Standardized mortality coefficient, standardized risk ratio, and years of potential life lost were calculated for the inhabitants of Botucatu who died after their 10th birthday, between January 1997 and March 1998, and classified according to their occupation and main cause of death. Occupational and medical information was obtained by interviewing families of the deceased and their doctors, and checking medical files. RESULTS: The standardized mortality coefficient ranged from 0.6 to 39.9 deaths/1000 workers in different occupations. The years of potential life lost ranged form 33 to 334 years/1000 workers. The ranking of causes of death varied according to occupation and the mortality risk considered. CONCLUSION: The risk measures analyzed showed a high heterogeneity when associated to occupation and causes of death, which reflects the great social inequality existingin the studied population.
Mortality risk measure inequalities among workers in Southeast Brazil
Keywords: Mortalidade; Ocupações; Coeficiente de mortalidade; Anos potenciais de vida perdidos; Mortality; Occupations; Mortality rate; Years of potential life lost